2001
DOI: 10.3354/meps222239
|View full text |Cite
|
Sign up to set email alerts
|

Can otolith chemistry detect the population structure of the shad hilsa Tenualosa ilisha? Comparison with the results of genetic and morphological studies

Abstract: The stock structure of the valuable tropical shad Tenualosa ilisha ('hilsa') has been studied in Bangladesh and India by analysing morphometric and genetic data. However, these studies had a narrow geographic scope and their results conflict. We made a comprehensive study of the stock structure of hilsa with otolith microchemistry in conjunction with complementary genetic and morphometric studies of the same fish. We examined the trace-element composition of the otolith cores of hilsa with laser-ablation induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 31 publications
8
46
0
Order By: Relevance
“…Ba is known to be correlated with biological activity on the overlying surface waters (Swan et al 2006) and also to increase in concentration with depth and distance from shore (Swan et al 2003a). High Li levels are thought to relate to input from hydrothermal activity (Bruland 1983) and to co-vary with salinity (Milton et al 1997, Campana et al 2000, Milton & Chenery 2001, Gillanders 2002, Rooker et al 2003. In the present study, Mn was found in highest concentrations in the Skagerrak and lowest on the MAR.…”
supporting
confidence: 48%
“…Ba is known to be correlated with biological activity on the overlying surface waters (Swan et al 2006) and also to increase in concentration with depth and distance from shore (Swan et al 2003a). High Li levels are thought to relate to input from hydrothermal activity (Bruland 1983) and to co-vary with salinity (Milton et al 1997, Campana et al 2000, Milton & Chenery 2001, Gillanders 2002, Rooker et al 2003. In the present study, Mn was found in highest concentrations in the Skagerrak and lowest on the MAR.…”
supporting
confidence: 48%
“…Hilsa from four regions in Bangladesh showed widespread movement among regions, and all fish examined had spent several months in water with marine Sr isotope ratios. The data supported previous findings [134,135] that hilsa from the remote population in Sylhet were distinct and showed that fish from the region had a common homing strategy. A study carried out by an American team [136] aimed to quantify the relative contribution of water and food to Sr and Ba deposited in otoliths of juvenile mummichogs (F. heteroclitus).…”
Section: Fish Productssupporting
confidence: 93%
“…To quantify these records and address a number of questions in marine ecology, researchers have utilized inductively coupled plasma mass spectrometry (ICPMS) (Campana 1999, Campana & Thorrold 2001. This approach has been used to differentiate among spawning stocks (Edmonds et al 1991, Milton & Chenery 2001a, Rooker et al 2001, identify individuals that utilized different nursery habitats , Forrester & Swearer 2002, Gillanders 2002, and discriminate between dispersed and retained larvae (Swearer et al 1999). However, to determine the natal site of an individual, the site where a given larva was spawned, 2 pieces of information are required: (1) a spatial atlas of otolith chemical signatures at natal sites, ideally generated using otoliths of near-term eggs or recently hatched larvae from multiple discrete sites prior to dispersal, and (2) the ability to measure that natal chemical signature from post-larval recruits.…”
Section: Introductionmentioning
confidence: 99%